2023
DOI: 10.1101/2023.09.16.558074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SECRET AGENT O-GlcNAcylates hundreds of proteins involved in diverse cellular processes in Arabidopsis

Ruben Shrestha,
Sumudu Karunadasa,
Tara Grismer
et al.

Abstract: O-GlcNAcylation is a critical post-translational modification of proteins observed in both plants and animals and plays a key role in growth and development. While considerable knowledge exists about over 3000 substrates in animals, our understanding of this modification in plants remains limited. Unlike animals, plants possess two putative homologs: SECRET AGENT (SEC) and SPINDLY (SPY), with SPY also exhibiting O-fucosylation activity. To investigate the role of SEC as a major O-GlcNAc transferase in plants, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Intracellular protein O -GlcNAcylation is catalyzed by an O -GlcNAc transferase (OGT), SECRET AGENT (SEC) that is a paralog of SPY in Arabidopsis 46 . Recent proteomic studies showed that SPY and SEC have unique targets as well as common targets in Arabidopsis 34,35,47,48 . The interplay between SPY and SEC is complex as these two types of glycosylation can interact antagonistically or additively, depending on the target proteins 32,38,46,49 .…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular protein O -GlcNAcylation is catalyzed by an O -GlcNAc transferase (OGT), SECRET AGENT (SEC) that is a paralog of SPY in Arabidopsis 46 . Recent proteomic studies showed that SPY and SEC have unique targets as well as common targets in Arabidopsis 34,35,47,48 . The interplay between SPY and SEC is complex as these two types of glycosylation can interact antagonistically or additively, depending on the target proteins 32,38,46,49 .…”
Section: Resultsmentioning
confidence: 99%